Principals’ Time Tabling Practices and School Effectiveness in Ilorin Metropolis Secondary Schools, Kwara State - Adeseko Sunday Olaifa; Balikis Abdulsalam; Rasheedat Modupe Oladimeji; Ebunlomo Oreoluwa Olaifa; Afeez Adesina Shittu (INCOME: Innovation of Economics and Management, 2025)
This study examined the correlation between principals' time-tabling practices and private secondary school effectiveness in Kwara State, Nigeria. Time-tabling practices, encompassing planning, allocation, implementation, and evaluation, are pivotal to optimizing school operations and achieving academic excellence. The study adopted a descriptive correlational research design, involving 276 teachers selected through multistage sampling from private secondary schools across Kwara State. Data were collected using a validated questionnaire, Principals’ Time-Tabling Practices and School Effectiveness Questionnaire (PTTPSEQ) and analyzed using Pearson’s Product-Moment Correlation at a 0.05 level of significance. Findings revealed that time-tabling planning and allocation practices were highly utilized by principals with implementation and evaluation practices moderately adopted. The level of school effectiveness in the sampled schools was found to be high, evidenced by strong academic outcomes, student engagement and positive teaching quality. However, areas such as resource allocation, infrastructure and extracurricular engagement showed room for improvement. Significant positive relationships were identified between time-tabling practices and school effectiveness, with planning practices exhibiting the strongest correlation (r = 0.779, p < 0.05). Allocation and implementation practices also significantly influenced school effectiveness (r = 0.539 and r = 0.276). These results underscore the critical role of well-structured time-tabling practices in enhancing school performance. The study recommends capacity-building programs for school administrators to optimize time-tabling processes and the integration of technology to streamline planning and scheduling. Continuous evaluation and stakeholder engagement in time-tabling decisions are also encouraged to ensure adaptability to evolving educational needs.